Cyclic Nucleotide-Specific Phosphodiesterases as Potential Drug Targets for Anti-Leishmania Therapy - Sebastián-Pérez, Victor (Antimicrob Agents Chemother, 2018)
The available treatments for leishmaniasis are less than optimal due to inadequate efficacy, toxic side effects, and the emergence of resistant strains, clearly endorsing the urgent need for discovery and development of novel drug candidates. Ideally, these should act via an alternative mechanism of action to avoid cross-resistance with the current drugs. As cyclic nucleotide-specific phosphodiesterases (PDEs) of Leishmania major have been postulated as putative drug targets, a series of potential inhibitors of Leishmania PDEs were explored. Several displayed potent and selective in vitro activity against L. infantum intracellular amastigotes. One imidazole derivative, compound 35, was shown to reduce the parasite loads in vivo and to increase the cellular cyclic AMP (cAMP) level at in a dose-dependent manner at just 2× and 5× the 50% inhibitory concentration (IC(50)), indicating a correlation between antileishmanial activity and increased cellular cAMP levels. Docking studies and molecular dynamics simulations pointed to imidazole 35 exerting its activity through PDE inhibition. This study establishes for the first time that inhibition of cAMP PDEs can potentially be exploited for new antileishmanial chemotherapy.